Identifying the 'Achilles heel' of type 1 diabetes. (22nd February 2021) - Battaglia, M; Buckner, J H; Levings, M K; Richardson, S J; Wong, F S; Tree, T I
Summary: When Thetis dipped her son Achilles into the River Styx to make him immortal, she held him by the heel, which was not submerged, and thus created a weak spot that proved deadly for Achilles. Millennia later, Achilles heel is part of today's lexicon meaning an area of weakness or a vulnerable spot that causes failure. Also implied is that an Achilles heel is often missed, forgotten or under-appreciated until it is under attack, and then failure is fatal. Paris killed Achilles with an arrow 'guided by the Gods'. Understanding the pathogenesis of type 1 diabetes (T1D) in order to direct therapy for prevention and treatment is a major goal of research into T1D. At the International Congress of the Immunology of Diabetes Society, 2018, five leading experts were asked to present the case for a particular cell/element that could represent 'the Achilles heel of T1D'. These included neutrophils, B cells, CD8 + T cells, regulatory CD4 + T cells, and enteroviruses, all of which have been proposed to play an important role in the pathogenesis of type 1 diabetes. Did a single entity emerge as 'the' Achilles heel of T1D? The arguments are summarized here, to make this case. Graphical Abstract: